The moving target of visualization software for an increasingly complex world. (April 2020) - Reina, Guido; Childs, Hank; Matković, Krešimir; Bühler, Katja; Waldner, Manuela; Pugmire, David; Kozlíková, Barbora; Ropinski, Timo; Ljung, Patric; Itoh, Takayuki; Gröller, Eduard; Krone, Michael
Highlights: Visualization research relies on software development Reward discrepancy exists between novel research and necessary software development Visualization software is hard to design, assess, compare, use and maintain Considerations on prototypes and extension/development of frameworks We give advice about, identify provisions for and discuss software in our community. Graphical abstract: Abstract: Visualization has evolved into a mature scientific field and it has also become widely accepted as a standard approach in diverse fields, including physics, life sciences, and business intelligence. However, despite its successful development, there are still many open research questions that require customized implementations in order to explore and establish concepts, and to perform experiments and take measurements. Many methods and tools have been developed and published but most are stand-alone prototypes and have not reached a mature state that can be used in a reliable manner by collaborating domain scientists or a wider audience. In this study, we discuss the challenges, solutions, and open research questions that affect the development of sophisticated, relevant, and novel scientific visualization solutions with minimum overheads. We summarize and discuss the results of a recent National Institute of Informatics Shonan seminar on these topics.